2021
DOI: 10.3389/fgene.2021.728250
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Potential of Nanoparticles: Structural and Functional Modifications in DNA

Abstract: The rapid advancement of nanotechnology enhances the production of different nanoparticles that meet the demand of various fields like biomedical sciences, industrial, material sciences and biotechnology, etc. This technological development increases the chances of nanoparticles exposure to human beings, which can threaten their health. It is well known that various cellular processes (transcription, translation, and replication during cell proliferation, cell cycle, cell differentiation) in which genetic mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 135 publications
1
21
0
1
Order By: Relevance
“…This is probably due to the five-fold higher concentration of AgNPs used (50-100 mg•L −1 ). Our findings confirm the genotoxic character of nanoparticles, also described by other authors [41], particularly if applied at a high concentration. It can also be suggested that AgNPs have a higher mutagenic potential than the gold nanoparticles that induced variation only in 7.5% of Lamprocapnos spectabilis (L.) Fukuhara plants at 100 mg•L −1 concentration [42].…”
Section: Effect Of Silver Nanoparticles On the Genetic Stabilitysupporting
confidence: 93%
“…This is probably due to the five-fold higher concentration of AgNPs used (50-100 mg•L −1 ). Our findings confirm the genotoxic character of nanoparticles, also described by other authors [41], particularly if applied at a high concentration. It can also be suggested that AgNPs have a higher mutagenic potential than the gold nanoparticles that induced variation only in 7.5% of Lamprocapnos spectabilis (L.) Fukuhara plants at 100 mg•L −1 concentration [42].…”
Section: Effect Of Silver Nanoparticles On the Genetic Stabilitysupporting
confidence: 93%
“…Genotoxicity, the damage to genetic materials, may lead to carcinogenesis and other chronic diseases. If germ cell DNA is compromised, it will affect the individual health and could also have an impact on the next generations [ 92 , 93 , 94 ]. Therefore, genotoxicity assessment is considered a crucial aspect of nanomaterial hazard identification.…”
Section: Genotoxicity and Epigeneticsmentioning
confidence: 99%
“…Therefore, genotoxicity assessment is considered a crucial aspect of nanomaterial hazard identification. The mode of nanomaterial-induced genotoxicity can be classified as direct primary (interaction between nanomaterial and genetic materials directly), indirect primary (nanomaterial-induced reactive nitrogen species (RNS)/ROS species affecting the genetic materials), and secondary (damage of genetic materials due to nanomaterial-induced inflammation) mechanisms [ 92 , 95 , 96 , 97 ]. Oxidative stress has been widely considered an underlying mechanism of nanomaterial-induced genotoxicity [ 92 , 94 , 98 , 99 ].…”
Section: Genotoxicity and Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics that make nanoparticles useful are also responsible for inducing toxic effects on aquatic organisms. Concerns about the effects on genotoxicity of NM have increased in the last years [108]. Carbon nanotube-induced genotoxicity can be ascribed to various factors such as direct interaction with cellular components, direct interaction of the particles with the DNA, the release of toxic ions and indirect destruction caused by ROS [109].…”
Section: Water Pollutionmentioning
confidence: 99%